Implementing coordinated ambulatory cardiology care in southern Germany: a mixed-methods study - Hennrich, Patrick; Bölter, Regine; Wensing, Michel (BMC health services research, 2019)
In 2009 health insurers AOK and Bosch BKK introduced the “FacharztProgramm Kardiologie” - a program for coordinated ambulatory cardiology care in the German state of Baden-Württemberg. It aims for efficient, medical guideline-oriented cardiology care to reduce avoidable hospitalizations as well as costs of care. A high number of cardiologists participate and the program has served as blueprint for programs in other medical fields. With many prerequisites and conditions involved, its implementation cannot be expected to be self-directed. Still, only little data on the actual implementation exists. We aimed to determine to what extent medical specialists and cooperating general practitioners implemented the program, which components they adapted, and which contextual factors they deemed relevant.
Gesehen am 27.01.2020